2021
DOI: 10.1101/2021.01.12.21249694
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal SARS-CoV-2 vaccine allocation using real-time seroprevalence estimates in Rhode Island and Massachusetts

Abstract: As three SARS-CoV-2 vaccines come to market in Europe and North America in the winter of 2020-2021, distribution networks will be in a race against a major epidemiological wave of SARS-CoV-2 that began in autumn 2020. Rapid and optimized vaccine allocation is critical during this time. With 95% efficacy reported for two of the vaccines, near-term public health needs require that distribution is prioritized to the elderly, health-care workers, teachers, essential workers, and individuals with co-morbidities put… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…We observed that in the absence of susceptibility-based targeting, interventions prioritising highly connected individuals were more effective early in the epidemic. Others have highlighted the importance of antibody testing to prevent infection and death, [10, 18] and our results further support this approach especially when targeting highly connected individuals late in an epidemic when a high proportion has already been infected. The proportion of healthcare workers with SARS-CoV-2 antibodies ranges between 2-50% in different settings, [19] based on our results, targeting the available doses based on previous immunity could maximise its impact especially in settings where seroprevalence is high.…”
Section: Discussionsupporting
confidence: 80%
“…We observed that in the absence of susceptibility-based targeting, interventions prioritising highly connected individuals were more effective early in the epidemic. Others have highlighted the importance of antibody testing to prevent infection and death, [10, 18] and our results further support this approach especially when targeting highly connected individuals late in an epidemic when a high proportion has already been infected. The proportion of healthcare workers with SARS-CoV-2 antibodies ranges between 2-50% in different settings, [19] based on our results, targeting the available doses based on previous immunity could maximise its impact especially in settings where seroprevalence is high.…”
Section: Discussionsupporting
confidence: 80%
“…Given that Madagascar has now experienced multiple waves of infection (www.covid19mg.org) and that estimates of seroprevalence from blood donors in Madagascar show elevated population immunity [23], we also investigated strategies to take previous infection and thus immunity into account. Unsurprisingly, vaccinating only seronegative individuals allows for doses to be reallocated and expand protection to a larger population [8,26,27]. However, we note that assessing seropositivity via rapid testing at health facilities could slow the speed of vaccine delivery, which, in situations of high seropositivity, could reduce benefits in terms of mortality reductions.…”
Section: Discussionmentioning
confidence: 95%
“…Serious side effects, such as allergic responses, have been recorded infrequently and no long-term consequences have been recorded [2,10]. The main outcomes of the trials will be monitored until August2021, while the secondary outcomes will be monitored until January 2023 Tran et al [11]. The vaccine was the first COVID-19 vaccine to be approved for emergency use by a strict regulatory authority [12] and the first to be licensed for routine use [13].…”
Section: Pfizer-biontechmentioning
confidence: 99%
“…Pfizer and BioNTech intended to produce around 2.5 billion doses in 2021 as of March30, 2021 [5]. BioNTech and Pfizer have agreed to pay around $3 billion in advance purchase agreements to offer a licensed vaccine in the United States, the European Union, the United Kingdom, Japan, Canada, Peru, Singapore, and Mexico [11]. Because the vaccine must be maintained at extremely low temperatures, distribution and storage are logistical challenges.…”
Section: Pfizer-biontechmentioning
confidence: 99%